The Forgotten Man : A new history of the Great Depression - Shlaes, Amity (New York : HarperCollins Publishers, 2007)
"It's difficult today to imagine how America survived the Great Depression. Only through the stories of the common people who struggled during that era can we really understand how the nation endured. These are the people at the heart of Amity Shlaes's history of one of the most crucial events of the twentieth century." "In The Forgotten Man, Amity Shlaes, one of the nation's most respected economic commentators, offers a reinterpretation of the Great Depression. Rejecting the old emphasis on the New Deal, she turns to the neglected and moving stories of individual Americans, and shows how through brave leadership they helped establish the steadfast character we developed as a nation. Some of those figures were well known, at least in their day - Andrew Mellon, the Greenspan of the era; Sam Insull of Chicago, hounded as a scapegoat. But there were also unknowns: the Schechters, a family of butchers in Brooklyn who dealt a stunning blow to the New Deal; Bill W., who founded Alcoholics Anonymous in the name of showing that small communities could help themselves; and Father Divine, a black charismatic who steered his thousands of followers through the Depression by preaching a Gospel of Plenty." "Shlaes also traces the mounting agony of the New Dealers themselves as they discovered their errors. She shows how both Presidents Hoover and Roosevelt failed to understand the prosperity of the 1920s and heaped massive burdens on the country that more than offset the benefit of New Deal programs. The real question about the Depression, she argues, is not whether Roosevelt ended it with World War II. It is why the Depression lasted so long. From 1929 to 1940, federal intervention helped to make the Depression great - in part by forgetting the men and women who sought to help one another."--BOOK JACKET.
Includes bibliographical references (p.421-438) and index.
Keywords: Depressions -- 1929 -- United States; New Deal, 1933-1939.; United States -- History -- 1919-1933.; United States -- History -- 1933-1945.; United States -- Social conditions -- 1933-1945.; United States -- Economic conditions -- 1918-1945.